The Ratio of Visceral to Subcutaneous Adipose Tissue Is Associated With Postoperative Anastomotic Leakage in Patients With Rectal Cancer With Gender Differences in Opposite Direction - Yan Luo; Jian Liu; Jiong Huang; Liya Ma; Zhen Li (Cancer Medicine, 2025)
ABSTRACT Background Anastomotic leakage (AL) is a severe postoperative complication in colorectal cancer and exerts negative impacts on patients' outcomes. Studies have found that body composition measured by CT images was associated with increased overall postoperative complications in colorectal cancer; however, few focused on postoperative AL in rectal cancer. This study aimed to explore the association between body composition parameters measured by CT images and postoperative AL in patients with rectal cancer, with an emphasis on subgroup analysis by gender. Methods From February 2014 to January 2020, a total of 444 patients with rectal adenocarcinoma who underwent radical proctectomy were included. Out of all patients, 21 developed AL after surgery. Body composition parameters, including the areas, mean CT values, height‐normalized indices of subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), intramuscular adipose tissue (IMAT) and skeletal muscle (SM) were derived from preoperative contrast‐enhanced arterial phase CT images at the third lumbar level. The ratio of visceral to subcutaneous adipose tissue (VSR) was calculated. Clinical and body composition parameters were compared between the AL group and the non‐AL group in all patients and separately in different genders. Results Body composition parameters were not significantly different in the AL group and the non‐AL group in all patients. However, most body composition parameters were significantly different between male and female patients. After separately analyzing by gender, VSR was significantly associated with postoperative AL in male and female. After multivariate regression, VSR remained an independent predictor for AL (OR: 0.1, p = 0.041 for male and OR: 39.1, p = 0.045 for female). Conclusion The VSR measured by CT images is an independent predictor for postoperative AL in patients with rectal cancer; however, it shows gender differences in opposite directions, serving as a protective factor in males, whereas as a risk factor in females.